ANALISIS EKONOMI USAHA MANDIRI NUGGET KULIT PISANG - Mahsun Ridlowi; Dwi Ari Cahyani (Jurnal Ilmiah Media Agrosains, 2020)
Nugget is one form of ready-to-food frozen food products, which is a product that has undergone heating until half-cooked (precooked), then frozen. Banana bark is the waste of banana fruit that can’t be made with optimal results. The nutrients contained in the peel of banana depends on the maturity of fruit and type and the banana fruit or plaintain banana has fewer fibers than ordinary bananas. The intention of this research is to know whether the business is worthy of banana peel nuggets to continue. This research uses Ambon banana peel in making nugget with extra sago flour, wheat flour, eggs and other spices. The research was conducted in the Polytechnic of Banjarnegara in November to December 2019. The method used by collecting data in the field and being tabulate-then transferred into the table form according to the needs of the analysis. For hypothesized testing tested with cost and profit analysis. The manufacture of banana leather nuggets includes selection of commodities, smoothing, material mixing, grinding, cutting, frying, topping, packing and marketing. Bananas selected are banana Ambon in a mature state that has a sweet flavor and the peel is soft. If the banana peel nugget sold Rp5.000,00 per package in order to get breakeven need to produce 115 packaging. From the results of the analysis obtained the ROI of the amount 9,86% which means the manufacture of the banana peel nugget will benefit Rp 9,86% for every Rp100,00 invested. From the results of the analysis of R/C ratio can be concluded that each expenditure of 1 rupiah resulted in revenues 1.09 rupiah, thereby then this business can be said to be feasible and can be developed. Kata kunci : analisis ekonomi, kulit pisang, nugget Abstrak Nugget merupakan salah satu bentuk produk makanan beku siap saji, yaitu produk yang telah mengalami pemanasan sampai setengah matang (precooked), kemudian dibekukan. Kulit pisang adalah limbah dari buah pisang yang belum bisa dimaanfatkan dengan hasil optimal. Tujuan penelitian ini adalah untuk mengetahui layak atau tidaknya usaha nugget kulit pisang untuk dilanjutkan. Penelitian ini menggunakan kulit pisang ambon dalam pembuatan nugget dengan tambahan tepung sagu, tepung terigu, telur dan bumbu lainnya. Penelitian dilaksanakan di Politeknik Banjarnegara pada bulan November hingga Desember 2019. Metode yang digunakan dengan mengumpulkan data di lapangan dan ditabulasikan, kemudian dipindahkan ke dalam bentuk tabelaris sesuai dengan kebutuhan analisis. Untuk pengujian hipotesisis diuji dengan analisis biaya dan keuntungan. Pembuatan nugget kulit pisang meliputi pemilihan komoditas, penghalusan, pencampuran bahan, pengukusan, pemotongan, penggorengan, pemberian topping, pengemasan dan pemasaran. Pisang yang dipilih merupakan pisang ambon dalam keadaan matang yang memiliki rasa manis dan kulitnya sudah lunak. Apabila nugget kulit pisang dijual Rp5.000,00 per kemasan agar mendapatkan titik impas perlu memproduksi 115 kemasan. Dari hasil perhitungan analisis diperoleh ROI sebesar 9,86% yang artinya pembuatan nugget kulit pisang ini akan mendapat keuntungan sebesar Rp 9,86% untuk setiap Rp100,00 yang diinvestasikan. Dari hasil analisis R/C ratio dapat disimpulkan bahwa setiap pengeluaran 1 rupiah menghasilkan pendapatan 1,09 rupiah, dengan demikian maka usaha ini dapat dikatakan layak dan dapat dikembangkan.